2020
DOI: 10.3390/app10113858
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of the Mechanical Response of Large Lattice Domains Using Homogenization and Design of Experiments

Abstract: Lattice-based workpieces contain patterned repetition of individuals of a basic topology (Schwarz, ortho-walls, gyroid, etc.) with each individual having distinct geometric grading. In the context of the design, analysis and manufacturing of lattice workpieces, the problem of rapidly assessing the mechanical behavior of large domains is relevant for pre-evaluation of designs. In this realm, two approaches can be identified: (1) numerical simulations which usually bring accuracy but limit the size of the domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several studies [8][9][10] have experimentally and/or numerically explored the structural response of metal-or polymer-based strut-and surface-based lattices, however only a few scrutinized FGLs [2,11,12]. To-date, finite element analyses of these structures have primarily focused on their elastic behaviour, despite lattice materials and FGLs offering great advantages over monolithic materials in terms of specific energy absorption [5], which is considerably high during their plastic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [8][9][10] have experimentally and/or numerically explored the structural response of metal-or polymer-based strut-and surface-based lattices, however only a few scrutinized FGLs [2,11,12]. To-date, finite element analyses of these structures have primarily focused on their elastic behaviour, despite lattice materials and FGLs offering great advantages over monolithic materials in terms of specific energy absorption [5], which is considerably high during their plastic response.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a good agreement of the FEN model with the experimental data. Besides the explicit geometric models, the homogenisation approach [12,[15][16][17][18][19] served as a computationally efficient alternative to determine the equivalent effective properties of a heterogeneous lattice. In [17,19], it was coupled with the modified Hill yield criterion and showed good agreement for variable density and surface-based lattices.…”
Section: Introductionmentioning
confidence: 99%